Comparison of the use of the laryngeal tube (vbm) and laryngeal mask airway under anaesthesia during spontaneous ventilation - Omar, Mahamarowi; Muhamad, Noor Zairul (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2005)
The purpose of this study is to assess whether the newly developed laryngeal tube {VBM) is a fast, reliable and easy device for airway management. We compared the use of the laryngeal tube (VBM) with the laryngeal mask airway in spontaneously ventilating adult patient undergoing general anesthesia and measured the easiness of insertion, incidence of airway trauma and sore throat and also the haemodynamic responses to insertion of these devices. A randomized single blinded prospective study was conducted involving a total of 121 premedicated, ASA 1 or 11 patients, aged 18 to 65 years and were divided into 2 groups either laryngeal tube {VBM) or laryngeal mask airway group as for airway man~gement during elective surgery. After a standardized induction of anaesthesia with fentanyl 1.5 ng.kg-1 and propofol 2 mg.kg-1, a size 3 or 4 laryngeal tube {VBM) or laryngeal mask airway was inserted and the patients breathed spontaneously throughout the surgery with no muscle relaxants given. Anaesthesia was maintained with nitrous oxide, oxygen and isoflurane. The airway device was removed at the end of surgery with the patients fully awake. The speed and ease of insertion and the number of attempts needed to successfully secure the airway were recorded. The incidence of airway trauma, sore throat and haemodynamic changes such as systolic blood pressure, diastolic blood pressure, mean arterial pressure and heart rate at different time intervals were recorded. Episodes of airway manipulations intraoperatively and end-tidal C02 at various time intervals were also recorded. We found that there was no statistically significant difference in time required for successful insertion and number of attempts for both groups. We were able to achieve a clear airway in 75.4% patients in L T group at the first attempt. There were no difference in incidence of airway trauma and sore throat between laryngeal tube and laryngeal mask airway. Both groups had no statistical differences in haemodynamic parameters during spontaneous ventilation under anaesthesia. Although, the incidence of airway manipulations and end - tidal C02 were higher with laryngeal tu~e (~BM) compared to the larynge~l mask airway but it is not likely to be clinically relevant 1n th1s study. We conclude that dunng spontaneous ventilation, the laryngeal tube (VBM) is a suitable alternative to the laryngeal mask airway.